Kinerja Pendapatan dan Belanja Daerah Kabupaten Pasuruan Tahun 2018-2023 - Rachma Ayu Wanodya; Danang Wibisono; Ibravita Dwi Annisa; Mayza Almanikma; Surur Fatma Ningtyas; Mega Tunjung Hapsari (Jurnal Riset Akuntansi, 2025)
This research effort aims to conduct a comprehensive analysis on the fiscal performance of Pasuruan Regency from 2018 to 2023 and to evaluate the efficiency of regional budget management. The results of the decentralization ratio calculation get an average of 20.92% with a sufficient performance. The results of the calculation of the expenditure growth ratio got an average of 3.45% with poor performance. The ratio of operational expenditure to capital expenditure received an average of 65.36% with good performance. The ratio of capital expenditure to total expenditure got an average of 13.16% with good performance. The ratio of direct and indirect spending to total spending has poor performance results. The tax effectiveness ratio got an average of 97.50% with quite effective performance. The results of this study are expected to be an input for the Pasuruan Regency government which aims to improve budget efficiency and strengthen regional financial autonomy.